2013
DOI: 10.1590/s1517-83822013005000068
|View full text |Cite
|
Sign up to set email alerts
|

Use of Plackett-Burman design for rapid screening of nitrogen and carbon sources for the production of lipase in solid state fermentation by Yarrowia lipolytica from mustard oil cake (Brassica napus)

Abstract: Mustard oil cake (Brassica napus), the residue obtained after extraction of mustard oil from mustard oil seeds, was investigated for the production of lipase under solid state fermentation (SSF) using the marine yeast Yarrowia lipolytica NCIM 3589. Process parameters such as incubation time, biomass concentration, initial moisture content, carbon source concentration and nitrogen source concentration of the medium were optimized. Screening of ten nitrogen and five carbon sources has been accomplished with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 23 publications
2
25
0
Order By: Relevance
“…Ushio et al, (1996) also optimized 1.0ml of inoculum for maximum lipase production [50]. Imandi et al, (2013) reported a 2ml of inoculums [51,52].…”
Section: Effect Of Inoculum Sizementioning
confidence: 99%
“…Ushio et al, (1996) also optimized 1.0ml of inoculum for maximum lipase production [50]. Imandi et al, (2013) reported a 2ml of inoculums [51,52].…”
Section: Effect Of Inoculum Sizementioning
confidence: 99%
“…Many substrates such as rice bran [80], coconut oil cake [65], olive cake and sugar cane bagasse [81], gingelly oil cake [67], babassu oil cake [74], wheat bran [82], Jatropha curcas seed cake [83], niger seed oil cake [84], palm kernal cake [84], groundnut oil cake [85] and mustard oil cake [86] have been used successfully for lipase production. The most important process parameters that have been investigated and optimized up to now are the incubation time, inoculum age, inoculum size, initial moisture content, nature and concentration of carbon and nitrogen sources as well as the C/N ratio of the medium [87].…”
Section: Solid Media Solid Support and Ambient Factors Used For Lipamentioning
confidence: 99%
“…In general, the moisture content used in SSF processes vary between 30 and 85% [91]. The influence of initial moisture content on lipase production by Y. lipolytica from niger seed oil cake was studied in the range of 50 to 100% (v/w) [84]. An initial moisture content of 60% (v/w) lead to the maximal value of lipase production (18.5 Ug -1 ).…”
Section: Solid Media Solid Support and Ambient Factors Used For Lipamentioning
confidence: 99%
See 2 more Smart Citations